Al-Ta2O5-GaN Semiconductor Device Structure - Yeoh, Lai Seng (2014)

(untitled)
GaN-based semiconductor devices have been extensively investigated for used in high power and high temperature device applications in order to replace Si which is no longer capable to fulfill these ever-increasing demands. The characteristics of low leakage current, low oxide charge density, and high oxide capacitance would be necessary for device-quality GaN-based MOS devices. Peranti semikonduktor berasaskan GaN telah dikaji secara menyeluruh bagi penggunaan dalam kuasa dan suhu tinggi bagi menggantikan Si yang tidak dapat lagi memenuhi keperluan tersebut. Sifat seperti kebocoran arus yang rendah, ketumpatan cas oksida yang rendah, dan kapasitan yang tinggi amat diperlukan untuk peranti MOS berasaskan GaN berkualiti tinggi.